Botnet detection In IoT devices using machine learning - Rouf, Shakir; Akash, Nazmus Sakib; Chowdhury, Amlan; Jahan, Sigma (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science, 2019.